Understanding intra-individual isotopic variability in modern cremated human remains for forensic and archaeological studies - Christophe Snoeck; Melanie M. Beasley; Dawnie Wolfe Steadman (PLoS ONE, 2025)
Cremated bone fragments can be studied using structural, elemental, and isotope analyses in archaeological contexts to reconstruct funerary practices and understand past mobility and migrations of populations that practiced cremation. However, the potential of isotope analyses of cremated bone in forensic contexts remains heavily unexplored. The identification of fire victims can be complex as the remains can be extremely fragmented and commingled. The high temperatures (up to 1000°C and above) destroy most organic matter such that, obtaining reliable DNA from such intensively burned human remains is extremely difficult. Still, other signals present in bone, such as strontium concentrations and isotopes, are preserved during cremation, and could be used to assess the geographical origin of unidentified fire-affected individuals. Carbon and oxygen isotope ratios together with infrared analyses provide information about the burning conditions and could help understanding how a body was burned. Here, isotope and infrared analyses are carried out on fourteen recently deceased cremated individuals of known residential history from the UTK Donated Skeletal Collection curated by the Forensic Anthropology Center (Knoxville, Tennessee). By carrying out these measurements on different bones with different turnover rates (i.e., otic capsule of the petrous part of the temporal bone, femur, and rib), we endeavor to reconstruct life histories of recently deceased cremated individuals and gain new insights into cremation practices. The results highlight differences in carbon and oxygen isotopes between different skeletal elements and confirm their potential to gather information about the way a body was burned (e.g., temperatures, fuel used). Strontium concentrations and isotope ratios were also measured to assess the geographical origin of these individuals. The use of strontium isotope ratios, however, seem to have limitations for individuals born in the last few decades due to globalization of consumed food resources. Nevertheless, it is still possible to obtain information about the birthplace of older individuals (> 50 years) by analyzing strontium isotope ratios in the petrous part of their temporal bone, which retains a signal linked to the first few years of their lives when local resources were still used in larger quantities compared to today.